2016
DOI: 10.5604/12303666.1168239
|View full text |Cite
|
Sign up to set email alerts
|

Improving Productivity in the Apparel Industry Through Gain Sharing and Continuous Process Improvement: the Case of a Serbian Manufacturer

Abstract: This paper analyses the effects of combined implementation of gain sharing wage incentives and continuous process improvement on productivity growth in the apparel industry. Results were obtained through empirical research conducted in a Serbian apparel manufacturer-Javor. A five step research approach was designed and applied in Javor, where productivity was continuously measured over a five year period. Results show a significant increase in productivity in Javor by the end of the fifth year, even though pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…Es por ello que las industrias hoy en día deben cumplir con los requisitos mencionados en el tiempo establecido, cosa que en los últimos años se ha visto afectada por la disminución de la eficiencia de producción. El principal problema que presentan estas empresas son la falta de mantenimiento y la deficiencia en los procesos de producción debido a que cada año se vuelve más complejos mantener los estándares si no estás en constante mejora [6], lo que conlleva a que un mal ambiente de trabajo genera retrasos en los procesos productivos [7]. Adicional a ello otros problemas que presentan el sector son fallas de máquinas [8], tiempos muerto o paradas inesperadas [9].…”
Section: A Modelo De Aumento De Eficiencia De Producción En El Rubrounclassified
See 2 more Smart Citations
“…Es por ello que las industrias hoy en día deben cumplir con los requisitos mencionados en el tiempo establecido, cosa que en los últimos años se ha visto afectada por la disminución de la eficiencia de producción. El principal problema que presentan estas empresas son la falta de mantenimiento y la deficiencia en los procesos de producción debido a que cada año se vuelve más complejos mantener los estándares si no estás en constante mejora [6], lo que conlleva a que un mal ambiente de trabajo genera retrasos en los procesos productivos [7]. Adicional a ello otros problemas que presentan el sector son fallas de máquinas [8], tiempos muerto o paradas inesperadas [9].…”
Section: A Modelo De Aumento De Eficiencia De Producción En El Rubrounclassified
“…Finalmente, en la actualidad existen varias técnicas que ayudan a eliminar los problemas mencionados pero la mayoría ataca problemas específicos y no se enfocan en todo sistema de la empresa. Las técnicas más resaltantes y de mayor resultado utilizadas para eliminar problemas de baja eficiencia de producción son las herramientas del mantenimiento para poder aumentar la capacidad de los procesos y reducir los fallos relacionados a las máquinas [6] y la redistribución de planta [10] para reducir tiempos improductivos por parte del personal.…”
Section: A Modelo De Aumento De Eficiencia De Producción En El Rubrounclassified
See 1 more Smart Citation
“…Quddus and Ahsan (2014) implemented KAIZEN on the sewing floor and on investigation, it was indicated that efficiency was increased (from 50% to 62%) whereas, wastes and defects were reduced (Quddus & Ahsan, 2014). Slović et al, (2016) analysed the impact of combined implementation of gain sharing wage incentives and continuous process improvement at apparel industry of Serbia; it was indicated that there was significant increase in productivity. The research was concluded that wage incentives can be used as efficient tool for motivating employees to play their role in improvement efforts (Slović et al, 2016).…”
Section: Introduction and Literaturementioning
confidence: 99%
“…Slović et al, (2016) analysed the impact of combined implementation of gain sharing wage incentives and continuous process improvement at apparel industry of Serbia; it was indicated that there was significant increase in productivity. The research was concluded that wage incentives can be used as efficient tool for motivating employees to play their role in improvement efforts (Slović et al, 2016). Syduzzaman and Golder (2015) calculated the layout plans for three different products and due to that workers' efficiency was increased i.e.…”
Section: Introduction and Literaturementioning
confidence: 99%